Critical Adult Learning of Immigrant Workers: A Social Network Perspective - Moosung Lee (Adult Education Research Conference, 2006)
Why does one immigrant worker get involved in critical learning whereas another does not? This study attempted to answer the question by revealing how social ties of immigrant workers play a key role in mediating critical learning to a particular political attitude. The results of the study suggested that immigrant workers who showed a resistant political attitude, which is linked to the process of critical learning, tended to have more social ties and occupy more important socio-structural positions in their network than other peer workers.
Keywords: Immigrant workers; critical learning; social structures